Dispositivo de cuidado no Núcleo de Apoio à Saúde da Família: experimentação com um grupo de pais - Santos, Patrícia Rocha dos (2018)
This study, involving participant observation, was limited to a brief intervention with a group of parents of patients undergoing phonoaudiological assessment in the Atenção Básica à Saúde (Primary Health Care System), more specifically in a Núcleo de Apoio à Saúde da Família (Family Health Support Center) in the municipality of Mauá, São Paulo. The hypothesis of this study is that pediatric speech therapy should not be directed exclusively to children but also to their families, taking into account the parents and other family dynamics. Objective: to identify the perceptions and ways in which parents relate to their children, noting affects that are at play while contributing to their development, with respect to identifying family problems and collaboration for the continuity of care, especially that which relates to the language alterations that led to the complaint and the demand for the health service. Method: the case study was set up as a brief group intervention and was carried out in seven in-person meetings. The meetings were documented using audio recordings. Meetings were later transcribed and interpreted by means of therapeutic scores and an analysis of parent discussions, relative to the emblematic situations experienced in the group. The ethical principles of research involving human subjects have been followed. Results and discussion: the group experiment allowed for a therapeutic "space/time" in spite of the limits on scale and time. The experiment was able to identify and validate the anxieties and sufferings of the parents who participated. It was therapeutic because it created caring relationships, identified challenges and helped to improve the ways in which parents interact with their children, and offered opportunities for clinical listening. This researcher was able to avoid relying entirely on the specificity of one discipline (that of speech therapy), although it was the foundation of this study. Conclusion: the group experiment provided evidence that understanding and problematizing parental perception about the speech and language disorders of their children is useful in understanding the clinical picture of these children. Additionally, the study contributes to a better understanding of the structure and the quality of care offered by the Atenção Básica à Saúde, as well as the relationship between the work of the Estratégia de Saúde da Família teams and the support of the Núcleo de Apoio à Saúde da Família